Hypothesis: calcium carbonate as phosphate binder: the fallacy of relying on serum phosphorus - Bommer, Jürgen; Ritz, Eberhard (Nephrology, dialysis, transplantation, 2010)
Both high phosphate intake and hyperphosphataemia are associated with an increased risk of vascular calcification and other soft-tissue calcification. The dietary phosphorus content is related to the dietary protein content. It is unacceptable to reduce protein intake in order to lower serum phosphorus concentration because of the risk of malnutrition, resulting in a negative protein balance. Apart from longer or more frequent dialysis sessions, the only possible alternative is to reduce phosphorus absorption in the gut. This can be achieved either by phosphate binders or—more recently—by inhibitors of the transfer of phosphorus across the intestinal wall [12].
Gesehen am 08.02.2023